'Being brave' - a case study of how an innovative peer review approach led to service improvement. Issue 4 (15th August 2016) - Mangan, Catherine; Pietroni, Mark; Porter, Denise
Abstract : Purpose: This article reports on the use of an innovative peer review approach to identifying and addressing the causes of inappropriate admissions from hospital to nursing homes in South Gloucestershire. It explains the methodology that was developed, the findings of the peer review process and reflects on the effectiveness of the process. Design/methodology/approach: The peer review consisted of two stages. The first stage involved a panel of local stakeholders carrying out an audit of a random selection of cases where people had been assessed as needing permanent nursing or residential care. From this four cases of inappropriate admissions were identified. Stage two involved an externally facilitated process with two peer challenge panels; one of local stakeholders and the other external experts. The two panels analysed the cases of inappropriate admissions, identified the system causes and suggested actions to tackle the issues which were fed back to an audience of local stakeholders. Findings: The combination of case audit and peer review was successful in providing robust challenge to the processes in South Gloucestershire by identifying shortcomings in the system and suggesting actions to improve outcomes. Research limitations/implications: The approach was taken in one council area and therefore may not be replicable in another area. Practical implications: The case study suggests that a peer review approach using both local and external peers, including providers, is an effective way to identify weaknesses in the health and social care processes. The insights offered by external peers and providers is helpful for councils in identifying where to focus resources and suggests that other areas should consider proactive adaptations to the peer review methodology that is offered as part of the LGA's programme of sector led improvement. Originality/value: The case study offers an innovative and original use of the peer review approach in social care that can be shared with other councils and partners. The South west improvement board have identified it as of particular interest to other areas seeking to work with partners to identify and implement positive change.